Green Hydrogen Production from Biomass-Derived Syngas Using Advanced Membrane Separation Technologies - Brahmansa Husin; Haykal Prakusuma; Anita setiawati (International Journal of Energy Systems and Materials Innovation, 2025)
The global shift toward low-carbon energy systems has positioned green hydrogen as a pivotal component for achieving industrial decarbonization. Among various production pathways, hydrogen generation from biomass gasification presents a renewable and carbon-neutral alternative; however, its large-scale application remains limited by challenges in syngas purification and process integration. This study investigates the development and performance of advanced mixed-matrix membranes (MM-MOF) incorporated into water–gas shift (WGS) membrane reactors to enhance hydrogen separation efficiency, thermal stability, and economic feasibility. Hybrid polymer–MOF composite membranes with varied filler loadings (5%, 15%, and 30%) were synthesized and tested using biomass-derived syngas under controlled conditions (450 °C, 10 bar, S/C = 2). The optimal MM-MOF membrane with 30 wt% filler achieved a hydrogen permeance of 1.05 × 10⁻⁷ mol m⁻² s⁻¹ Pa⁻¹ and an H₂/CO₂ selectivity of 95, leading to 88.9% CO conversion and 97.0% hydrogen purity. Durability tests confirmed excellent long-term stability with only 15% permeance decline after 500 hours, outperforming conventional Pd–Ag membranes. Techno-economic analysis revealed that the integrated system reduced the Levelized Cost of Hydrogen (LCOH) to approximately 1.95 USD/kg H₂ and lowered the global warming potential (GWP100) to 1.8 kg CO₂-eq/kg H₂, signifying substantial economic and environmental benefits. Overall, the results indicate that MM-MOF-based membrane reactors provide an efficient, durable, and cost-effective route for hydrogen production from biomass syngas, supporting the transition toward circular and low-carbon energy systems.